Anisakis pegreffii impacts differentiation and function of human dendritic cells. (25th April 2018) - Napoletano, C.; Mattiucci, S.; Colantoni, A.; Battisti, F.; Zizzari, I. G.; Rahimi, H.; Nuti, M.; Rughetti, A.
Summary: Human dendritic cells (DCs) show remarkable phenotypic changes when matured in the presence of helminth‐derived products. These modifications frequently elicited a polarization towards Th2 cells and regulatory T cells thus contributing to immunological tolerance against these pathogens. In this study, the interaction between DCs and larvae of the zoonotic anisakid nematode Anisakis pegreffii was investigated. A. pegreffii larvae were collected from fish hosts, and monocyte‐derived DCs were cocultured in the presence of the live larvae (L) or its crude extracts (CE). In both experimental conditions, A. pegreffii impacted DC viability, hampered DC maturation by reducing the expression of molecules involved in antigen presentation and migration (ie HLA‐DR, CD86, CD83 and CCR7), increased the phagosomal radical oxygen species (ROS) levels and modulated the phosphorylation of ERK1, 2 pathway. These biological changes were accompanied by the impairment of DCs to activate a T‐cell‐mediated IFNγ. Interestingly, live larvae appeared to differently modulate DC secretion of cytokines and chemokines as compared to CE. These results demonstrate, for the first time, the immunomodulatory role of A. pegreffii on DCs biology and functions. In addition, they suggest a dynamic contribution of DCs to the induction and maintenance of the inflammatory response against A. pegreffii .